2021
DOI: 10.2147/ijn.s289707
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Conversion and Removal of Manganese Ferrite Nanoparticles in RAW264.7 Cells and Induced Alteration of Metal Transporter Gene Expression

Abstract: Background: Manganese Ferrite Nanoparticles (Mn-IONPs) are widely used in biomedical field and their cytotoxicity has been initially explored, but the mechanism remains obscure. The nano-bio interactions are believed to be crucial for cytotoxicity mechanism, while little data have been acquired. Methods: Mn-IONPs were synthesized by thermal decomposition of acetylacetonate precursor. After physicochemical characterization, we analyzed the metabolic conversion and removal of Mn-IONPs in RAW264.7 cells by Prussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In addition, manganese can be consumed in the amount of 0.67-4.99 mg, with a mean value of 2.21 mg/day [9], and recently the Mn 2+ released concentration from 3 to 18 nm nanoparticles was demonstrated to be in the range of safe doses [10]. Yet, as its cytotoxicity is still of concern [11], other chemical compositions, such as ferrites doped with calcium, have recently been proposed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, manganese can be consumed in the amount of 0.67-4.99 mg, with a mean value of 2.21 mg/day [9], and recently the Mn 2+ released concentration from 3 to 18 nm nanoparticles was demonstrated to be in the range of safe doses [10]. Yet, as its cytotoxicity is still of concern [11], other chemical compositions, such as ferrites doped with calcium, have recently been proposed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Regions of intracellularly compartmentalized ferumoxytol NPs (such as those present in MMTV-PymT tumors) showed predominant T2, but little or no T1, enhancement ( Figure 2 ). Ferumoxytol imaging in a pilot study on patients showed similar findings [ 24 ].…”
Section: Immunotherapies and The Role Of Nps In Targeting Macrophagesmentioning
confidence: 64%
“…Furthermore, nanoparticles were detectable in the cytoplasm after 24 h ( 51 ). Some research suggested that nanoparticles continue to degrade within the cells over time ( 52 ).…”
Section: Resultsmentioning
confidence: 99%